Efficient capture of radioactive iodine by Ag-attached silica gel and its kinetics. (October 2022) - Wang, Junjun; Li, Mengchen; Feng, Yaxin; Liu, Yi; Liu, Junteng
Highlights: The removal rate of iodine by self-made Ag-attached silica gel is 98.62 % (wt.%). By selecting the intake air flow and humidity, the adsorption effect of silica gel can be changed. For the design of Ag-attached silica gel adsorption column, selecting a larger inlet flow can improve the utilization rate of adsorption column. The height of the packing layer in the adsorption column increases the mass transfer resistance, and changing the height can make the adsorption more complete. Humidity has no effect on the adsorption of gaseous iodine on Ag-attached silica gel. Yoon Nelson model can better simulate the dynamic adsorption behavior in the adsorption column of this experiment. Abstract: In order to absorb the radioactive iodine produced during the reprocessing of spent fuel in nuclear power plants, in this study, the self-made silver content of 2–8 % Ag-attached silica gel was used as the adsorbent to adsorb radioactive iodine. Through dynamic adsorption method discussed with Ag-attached silica gel by the total flow at the inlet, the packing layer height in adsorption column under the factors such as temperature, humidity and adsorption of gaseous iodine adsorption effect. The experimental conclusions show that the saturated adsorption capacity is almost not affected by the different inlet flow rate, and the mass transfer resistance of the adsorption column increases under the condition of small inlet flow rate, resulting in longer adsorption time and more saturated adsorption. The height of Ag-attached silica gel packing layer in the adsorption column has little effect on the mass transfer resistance, and its saturated adsorption capacity increases with the increase of packing layer height. The adsorption effect is almost the same under different humidity. Under the same other conditions, by isothermal adsorption of Ag-attached silica gel at different temperatures, it can be found that the adsorption effect of Ag-attached silica gel at 150 °C is the best, which is consistent with the literature referred to. Through the kinetic simulation of silica gel with several different adsorption models, it can be found that the Yoon-Nelson model can well fit the dynamic adsorption process of gaseous iodine on silica gel with silver content of 2–8 %. The dynamic adsorption of iodine on silica gel shows that the adsorption capacity of gaseous iodine on silica gel is 40.60–238.83 mg/g. Moreover, Ag-attached silica gel has stable properties and lower cost than other sorbents. It is a promising adsorbent and can be widely used for radioactive iodine generated in the post-processing of spent fuel.